Formas de aplicação e tipos de corretivo da acidez do solo: alterações nos atributos químicos em profundidade em longo prazo - Vargas, Jocelina Paranhos Rosa de (2017)
The main interest of the soils acidity correction is to neutralize the exchangeable Al3+, since the presence of this form of Al in the soil causes restriction of root growth and consequently the decrease of the productivity of sensitive crops. Thus, monitoring the advance of attributes related to soil acidity in depth in cultivated areas is fundamental to assist in the decision of reapplication of acidity corrective forms. The aim of this study was to quantify the chemical changes in the soil caused by lime application with different Ca:Mg ratios, in a superficial and incorporated form after 141 months of its application. The experiment was installed in 2004 under native field in an Ultisol. The statistical design was a two-factor type with two types of application forms (incorporated and superficial) and five types of correctives (control, and calcareous with Ca:Mg molar ratio of 30.0 (calcitic); 9.0; 5.0 and 3.2 (dolomitic). In July 2016, 36 trenches were opened in each plot and soil samples were collected at depths of 0 to 60 cm. In the soil layer of 0 to 10 cm the soil samples were collected every 1 cm, in the layer of 10 to 25 cm the soil samples were collected every 2.5 cm and in the layer of 25 to 60 cm the samples of were collected every 5 cm. In total, 25 depths per trench were sampled, totaling 828 soil samples used for the chemical analyzes. The analysis performed were: values of pH in water in the ratio 1:1, TSM index (Santa Maria Buffer) and Ca, Mg and Al exchangeable. From these results the saturation by Al and bases was calculated. The simple deposition of the dolomitic corrective on the surface of the soil, twelve years after the application, allowed changes in the attributes related to soil acidity in the profile, similar to the incorporation. The use of the calcitic corrective provided more significant alterations in the attributes related to soil acidity in the profile compared to the dolomite, following its greater solubility in relation to dolomite. Almost twelve years after the natural acidity correction of the soil following the recommendations of the Soil Chemistry and Fertility Commission -RS / SC (2016), a slight reacidification of the soil of the 0-5 cm layer is observed, whose aluminum saturation is still less than 5% in the first 10 cm. Even almost twelve years after the corrective application, superficial or incorporated, still significant migration of the alkalinizing front in the soil profile to depths greater than 20 cm is perceived.